2016
DOI: 10.1038/sj.bdj.2016.334
|View full text |Cite
|
Sign up to set email alerts
|

A study to explore specific stressors and coping strategies in primary dental care practice

Abstract: Background and Aims: It is widely acknowledged that dentists experience occupational stress. This qualitative study aimed to explore previously identified specific stressors in more detail in order to inform the development of a future stress management programme. Method: Two focus groups of dentists (N: 7 & 6) were conducted to explore, in more detail, nine specific stressors and concepts; being out of one's comfort zone, zoning out from the patient, celebrating the positive aspects of work, thinking aloud, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 58 publications
4
39
0
2
Order By: Relevance
“…Dentists Anxieties in Clinical Situation Scale (DACSS) -A pool of 30 items was generated based on the stressors revealed by previous research. eg 4,6,7,36 The subjective importance of the stressors to dentists, as revealed by a previous study, 7 influenced the final choice of 20 items for inclusion, which was made by the 3 researchers in committee. For each of the 20 items, dentists were asked to rate their anxiety on an 11 point Likert scale anchored 0 (not at all) & 10 (the most intense emotion you can experience).…”
Section: Questionnairesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dentists Anxieties in Clinical Situation Scale (DACSS) -A pool of 30 items was generated based on the stressors revealed by previous research. eg 4,6,7,36 The subjective importance of the stressors to dentists, as revealed by a previous study, 7 influenced the final choice of 20 items for inclusion, which was made by the 3 researchers in committee. For each of the 20 items, dentists were asked to rate their anxiety on an 11 point Likert scale anchored 0 (not at all) & 10 (the most intense emotion you can experience).…”
Section: Questionnairesmentioning
confidence: 99%
“…In the dental context, stress has been implicitly associated with anxiety and worry-type emotions. However, Chapman and colleagues [6][7][8] reported that stress may be accompanied by a variety of negative emotions such as frustration and guilt.…”
Section: Introductionmentioning
confidence: 99%
“…Occupational stress with high risks of burnout is widely acknowledged amongst dental practitioners, especially in those who work in the NHS. [3][4][5] Although musculoskeletal diseases were the most commonly reported cause of ill-health retirement in the paper, 1 only 12% of cases (n = 30) were so related within the OPRA dataset. Interestingly, 37 cases (15%) that were reported by OPs were cases related to either dermatological or respiratory causes, suggesting different risks leading to a wide range of WRIH conditions.…”
Section: An Underestimationmentioning
confidence: 99%
“…Women in this area also have a misconstrued belief that chewing tobacco increases energy for daily labour in the face of limited food intake and to suppress hunger. 4 Easy availability, poor socio-economic status, illiteracy and the low cost of the SLT are other key factors that promotes SLT use by women. 4 Moreover, the use of tobacco-based dentifrices (mishri, gul and lal dant manjan) further aggravates the problem.…”
Section: Appealing To Five Sensesmentioning
confidence: 99%
See 1 more Smart Citation